OPEN AND DISTANCE LEARNING STUDENTS’ PARTICIPATION IN A SELF-REGULATED LEARNING ENVIRONMENT WITHIN THE LEARNING MANAGEMENT SYSTEM - Christnalter Bunsu; Noor Dayana Abd Halim, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Open and Distance Learning (ODL) provides an alternative path for higher education, particularly beneficial for individuals who are unable to attend university full-time on campus, offering the benefits of flexibility, accessibility, and self-directed learning. With ongoing advancements in technology, ODL is becoming more relevant and expands educational access to a wider range of learners across the world. At the same time, distance learning promotes Self-Regulated Learning (SRL) and lifelong learning through the use of technology, often facilitated by Learning Management Systems (LMS). However, one concerning issue is that students have been observed to employ only a limited and suboptimal range of SRL strategies in online learning environments. Past studies have highlighted several common issues, including the digital divide, challenges with self-regulation, and a lack of essential SRL skills. Therefore, this research applied the design of an SRL environment in LMS to encourage effective SRL strategy utilization among ODL students and assessed their participation. Master’s students in an Open and Distance Learning (ODL) program at a public university were selected using convenient sampling, with a total of 23 students enrolled in an ODL course. The log data from LMS were analysed to assess students’ participation. Overall, the logs indicate a desirable level of participation across the SRL phases, with a significant increase in the Performance phase, suggesting that students were highly active during class activities and discussions. The high frequency of access also indicates active use of the LMS.